Enhancing oxidative stability and antioxidant retention through synergistic blending of rice bran oil and palm olein during prolonged deep-fat frying - Chotimarkorn, Chatchawan; Punvichai, Teerasak; Permpoonpattana, Patima; Pastsart, Umaporn (Journal of Food Technology Research, 2025)
Blending edible oils with complementary properties offers a practical strategy to enhance both frying stability and nutritional quality. This study investigated the oxidative stability, antioxidant retention, and fatty acid composition of rice bran oil (RBO), palm olein oil (POO), and their blends at 80:20 and 70:30 ratios during 30 hours of deep-fat frying at 180°C. A comprehensive analysis was conducted using key indicators such as peroxide value (PV), free fatty acids (FFA), p-anisidine value (p-AV), iodine value (IV), smoke point, tocopherols, tocotrienols, and γ-oryzanol content. The results showed that the 80:20 blend achieved the highest oxidative stability and antioxidant retention, with a 33.84% reduction in PV compared to POO and retention of 28.17 mg/100 g of γ-oryzanol after 30 hours. Both oil blends maintained a favorable SFA:MUFA: PUFA ratio of approximately 1:1.5:1, closely aligning with dietary recommendations for cardiovascular health. Blending effectively delayed lipid oxidation and thermal degradation compared to pure oils, resulting in better preservation of tocopherols and reduced formation of degradation products. These findings demonstrate that blending RBO and POO at appropriate ratios produces frying oils with improved thermal resistance and health-promoting attributes. This approach presents a cost-effective and scientifically grounded solution for industrial and household frying, offering improved product quality, safety, and nutritional value in fried foods.